ANALYSIS OF INDEPENDENT BOARDS AND CORPORATE SOCIAL RESPONSIBILITY WHICH IS INFLUENCED BY THE ROLE OF STAKEHOLDERS' MEDIATION IN INDONESIA - Dona Maydalena (Universitas Internasional Batam, 2024)
This study tries to find out how stakeholders' mediated roles affect independent boards and corporate social responsibility. This time, the independent board of commissioners, a CSR variable, is the research variable, and it is assessed using disclosure of the entity's social actions. For the 2017–2021 timeframe, a sample of 690 firms listed on the Indonesia Stock Exchange served as the research's sample. The author's research data came from financial and annual reports found on www.idx.co.id. The research approach used for this study's data analysis was panel regression. The study's findings demonstrate that independent board characteristics have a considerable negative impact on CSR reporting, which is tempered by stakeholder influence, expense, and ability.